Dynapenia and physical performance in community-dwelling elderly people in Japan - Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Nakashima, Hiroaki; Machino, Masaaki; Morozumi, Masayoshi; Kanbara, Shunsuke; Ito, Sadayuki; Inoue, Taro; Yamaguchi, Hidetoshi; Ishiguro, Naoki; Hasegawa, Yukiharu (Nagoya journal of medical science, 2020)
Aging of society has increased the incidence of physical disability. The goal of this study was to examine the physical ability of elderly people classified as having sarcopenia, presarcopenia, or dynapenia (a low muscle function without low muscle mass) in a community in Japan. The subjects were volunteers aged >60 years who were participants in a health checkup in Yakumo, Hokkaido and were in good general health. Demographic data were collected and physical performance tests were performed to measure grip strength, walking speed, back muscle strength, maximum stride length, and 3-m timed-up-and-go (3m TUG) time. A measurement of skeletal muscle mass was used as a basis for calculating the appendicular skeletal muscle index (aSMI). The rates of sarcopenia, presarcopenia, and dynapenia were 10%, 22%, and 8% in males (n=101, age 69.7±5.4 years), and 19%, 23%, and 13% in females (n=112, 68.5±5.9 years). Body mass index in subjects with dynapenia was significantly higher compared to that in subjects with sarcopenia and presarcopenia (p<0.01). Back muscle strength, maximum stride length and 3m TUG were similar in dynapenia and sarcopenia, but differed significantly with those in presarcopenia in both males and females without the influence of age (p<0.05). Further studies are needed to evaluate the benefits of dynapenia intervention programs and to explore the underlying pathophysiology of dynapenia.